2010
DOI: 10.1016/j.jcmg.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

First-Pass and Steady-State MR Angiography of Thoracic Vasculature in Children and Adolescents

Abstract: Magnetic resonance angiography (MRA) is an established noninvasive imaging modality for detection and evaluation of vascular pathologies in children with congenital heart disease. Standard first-pass (FP)-MRA uses a 3-dimensional MRA sequence with an extracellular contrast agent, in which spatial resolution is limited by breath-hold duration, and image quality (IQ) is limited by motion artifacts. The purpose of this study was to compare the diagnostic confidence, IQ, and image artifacts of standard FP-MRA to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…112 MRI may also be used as a tool to investigate aortic physiology. Quantification of stiffness, an important predictor of cardiovascular outcome, can be obtained with pulsewave measurements from high-temporal resolution cine imaging.…”
Section: G Mrimentioning
confidence: 99%
“…112 MRI may also be used as a tool to investigate aortic physiology. Quantification of stiffness, an important predictor of cardiovascular outcome, can be obtained with pulsewave measurements from high-temporal resolution cine imaging.…”
Section: G Mrimentioning
confidence: 99%
“…For FP-MRA, an ECG-gated, T1 weighted gradient-echo contrast-enhanced MRA (CE-MRA) [15,16] was carried out during intravenous injection of 0.03 mmol/kg of gadofosveset trisodium (Ablavar, Lantheus Medical Imaging, North Billerica, MA, USA). Images were acquired in the coronal orientation and contrast timing was achieved with the care bolus technique.…”
Section: Imaging Protocolmentioning
confidence: 99%
“…The overall objective therefore was to ascertain which MRA technique provided superior image quality during the steady state with a blood-pool agent in the setting of adult congenital heart diseases. Previous studies have shown gadofosveset trisodium to be effective in visualizing the thoracic vasculature in patients with congenital heart disease [15,16]. Naehle et al [16] compared conventional FP-MRA using gadofosveset trisodium with imaging in the SS phase using a T1-weighted 3D-IR sequence, similar to the IR-FLASH technique used in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Measurements were performed in large, medium-sized, and small intracranial arteries and veins, respectively, including the internal cerebral artery (A1), the middle cerebral artery (A2), and the proximal A3-segment of the anterior cerebral artery (A3) as well as the superior sagittal sinus (V1), the straight sinus (V2), and the inferior sagittal sinus (V3). To guarantee analysis at corresponding enhancement levels, we standardized dynamic time frames for quantitative measurements (3 seconds after initial arterial bolus arrival for all arterial vessels and 3 seconds after the initial venous bolus arrival for all venous vessels).…”
Section: Quantitative Analysismentioning
confidence: 99%